Bijak Bermedia Sosial dalam Perspektif Islam untuk Meningkatkan Literasi Digital kepada Masyarakat - Azkiya Elfaradisa Hanafi; Nurul Indah Ramadhani; Raden Muhammad Hilmi Maulana (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2026)
Social media's growth in the digital age has had a big impact on how people interact and communicate. Social media affects cognitive processes, behavior, and manners in daily life in addition to being a source of amusement and information. A number of detrimental effects, including hoaxes, cyberbullying, fake news, and slander, can result from careless social media use. In this article, a qualitative research method with a particular library-based research approach was employed. This research methodology combines various types of data, including books, scientific journal articles, the Quran and hadith, and other scientific literature related to Islamic digital media ethics. This research aims to study and analyze the application of Islamic teachings to digital media in contemporary society. Data collection techniques include a combination of document-focused and literature-based data collection. The results of the study indicate that Islam teaches its followers to always maintain morals and ethics in communicating, both directly and through digital media. Values ​​such as honesty, avoiding prejudice, not insulting others, and spreading kindness are important guidelines for using social media. By implementing Islamic values ​​on social media, social media should be used as a means to spread knowledge, preach, and good values, thereby creating a safe, harmonious, and ethical digital environment.